Pengaruh Modal Sosial dan Jaringan Bisnis Terhadap Pengembangan Usaha Bordir di Kota Tasikmalaya - Resky Ichsan Taufik; Alfin Nur Arifah; Rina Madyasari; Yudi Setia Rachmanda (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
The embroidery industry is one of the leading business sectors in Tasikmalaya City and has significant potential to support regional economic growth. However, many business owners still face limitations in utilizing social capital and developing business networks, resulting in less optimal business development. This study aims to examine the influence of Social Capital and Business Networks on the Development of Embroidery Businesses in Tasikmalaya City. This research employed a quantitative method with a survey approach. The population consisted of embroidery business owners in Tasikmalaya City, with a sample of 94 respondents selected using purposive sampling. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), F-test, and t-test with the assistance of IBM SPSS Statistics. The results indicate that Social Capital has a positive and significant effect on Business Development, with a regression coefficient of 0.356 and a significance value of 0.002. Business Networks also have a positive and significant effect on Business Development, with a regression coefficient of 0.463 and a significance value of 0.000. These findings suggest that stronger social capital and broader business networks contribute to higher levels of embroidery business development in Tasikmalaya City